Mucosal interplay among commensal and pathogenic bacteria : Lessons from flagellin and Toll-like receptor 5 - Rumbo, Martín (2006)
Toll-like receptors (TLR) detect pathogen-associated molecular patterns (PAMP) and play a crucial role in triggering immunity. Due to their large surfaces in direct contact with the environment, mucosal tissues are the major sites of PAMP-TLR signalling. How innate and adaptive immunity are triggered through flagellin-TLR5 interaction is the main focus of the review. In view of recent reports on genetic polymorphism, we will summarize the impact of TLR5 on the susceptibility to mucosal infections and on various immuno-pathologies. Finally, the contribution of TLRs in the induction and maintenance of mucosal homeostasis and commensal discrimination is discussed.